Factibilidad técnica para el aprovechamiento integral del camarón de la especie penaeus vannamei - Chávez Astudillo, David Roberto (2010)
The growth of the shrimp industry has generated a high percentage of waste represented by the head and shell. This project proposes a solution to harness these resources and help to reduce environmental impact caused during the packaging process by identifying suitable technological methods for processing waste, previously made a study of the availability and characterization of them. Concluding that Ecuador has the tools necessary to use the head and shell of shrimp, in obtaining chitosan, extraction of natural pigments, production of a seasoning powder and flour for animal consumption.